2012
DOI: 10.2139/ssrn.1352363
|View full text |Cite
|
Sign up to set email alerts
|

Buying Beauty: On Prices and Returns in the Art Market

Abstract: This paper investigates the evolution of prices and returns in the art market since the middle of the previous century. We first compile a comprehensive list of more than 10,000 artists and then build a dataset that contains information on more than 1.1 million auction sales of paintings, prints, and works on paper. We perform an extensive hedonic regression analysis that includes unique price-determining variables capturing amongst others: the artist's reputation, the strength of the attribution to an artist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 42 publications
(22 reference statements)
4
64
1
Order By: Relevance
“…The market is highly segmented and dominated by a few large auction houses, and only a small number of works are 3 Art is not only sold in auction but also privately, for example through dealers. Renneboog and Spaenjers (2013) note that it is generally accepted that auction prices set a benchmark that is also used in the private market. 4 An artwork is "bought in" when the highest bid does not reach the reserve price, and the artwork goes unsold.…”
Section: Data and Art Price Index Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The market is highly segmented and dominated by a few large auction houses, and only a small number of works are 3 Art is not only sold in auction but also privately, for example through dealers. Renneboog and Spaenjers (2013) note that it is generally accepted that auction prices set a benchmark that is also used in the private market. 4 An artwork is "bought in" when the highest bid does not reach the reserve price, and the artwork goes unsold.…”
Section: Data and Art Price Index Constructionmentioning
confidence: 99%
“…They reason this conclusion by assuming that the more established and famous auction houses will offer the 'best' work, while the less familiar and smaller ones will have less quality paintings (see also, Renneboog and Spaenjers, 2013). We assign those auction houses a separate dummy variable, i.e., a value of one indicates that the painting was auctioned by one of the leading auction houses: Christie's London or New York and Sotheby's London or New York.…”
Section: Data and Art Price Index Constructionmentioning
confidence: 99%
“…In the study of the artwork price model, the classic Hedonic regressive model is a semi-log model [15], which can be expressed as following: …”
Section: A the Construction Of Artwork Price Modelmentioning
confidence: 99%
“…Taylor constructed the price index of Australian aboriginal artwork by Hedonic price index and found that the high artwork yield is about 2% less than other artworks [14]. In addition, Renneboog et al analyzed and improved the Hedonic index method and applied it into the pricing, investment, and analysis of artwork market [15]- [18]. Nowadays, the Hedonic index method had gained a lot of achievements in the artwork pricing and investment.…”
Section: Introductionmentioning
confidence: 99%
“…In most hedonic regressions, authenticity dummies carry positive signs whereas indications that the artworks are not from the master himself carry negative signs. According to Renneboog and Spaenjers (2009) "whenever an attribution dummy comes into play, the average price level drops by more than 50%". Once fakes are discovered they are usually immediately removed from the market.…”
Section: Introductionmentioning
confidence: 99%